Forms of variable resistance training - McMaster, D. T.; Cronin, J.; McGuigan, M. (Strength and Conditioning Journal, 2009)
Resistance training methods have been broadly classified into 3 categories: Constant, accomodating and variable resistance. Variable resistance training methods which include cams and levers, chains and rubber-based resistance, will be the focus of this article. The kinematics, kinetics and human strength curve characteristics associated with these 3 types of variable resistance are discussed, given that each resistance type may offer a unique set of mechanical stimuli and hence musculoskeletal adaptations. The practical applications and limitations associated with each form of variable resistance will also be considered.